Post-Seismic Surface Deformation of The Tarakan Earthquake in 2015 Using The DInSAR Technique - Pertiwi, Imanuela Indah; Trismahargyono, Trismahargyono; Marniati, Marniati; Purba, Joshua (Department of Urban and Regional Planning, Diponegoro University, 2025)
Deformation can help predict the presence and severity of an earthquake. SAR image data can be used to calculate post-seismic surface deformation using the InSAR and DInSAR methods. DInSAR (Differential Interferometric Synthetic Aperture Radar) is a well-established technology for monitoring subsidence and uplift with millimeter precision. This study uses SAR imagery to detect surface deformation caused by a magnitude M 6.1 earthquake on December 21, 2015, at 01:47:37 WIB in Tarakan Regency, North Borneo. The data used is Sentinel-1 satellite imagery in SLC (single-look complex) format, with a master image from December 18, 2015 (3 days before the earthquake), and a slave image from January 11, 2016 (21 days after). The interferogram generated by the Tarakan earthquake shows deformation patterns radiating in three directions: northeast, southeast-southwest, and southwest-northwest. Tarakan City, located south-southwest of the epicenter, experienced the highest subsidence deformation of 0.001–0.035 meters. On December 21, 2015, the Tana Tidung I Regency area, 33 kilometers southwest of the epicenter, showed the highest uplift deformation (0.019–0.079 meters). The largest uplift in Tana Tidung II Regency (0.069 meters), about 10 kilometers north of the epicenter, occurred near the fault zone. Surface deformation due to the Tarakan earthquake contributes to seismic hazard assessment in North Borneo and indicates other locally active faults. Uplift to the east and subsidence to the west of the epicenter suggest an oblique-normal fault, with dominant strike-slip motion and normal (downward) fault blocks to the west.